Motivations for participation in higher education: narratives of non-traditional students at Makerere University in Uganda. Issue 1 (2nd January 2016) - Tumuheki, Peace Buhwamatsiko; Zeelen, Jacques; Openjuru, George Ladaah
Abstract: The objective of this qualitative study was to establish motivations for participation of non-traditional students (NTS) in university education. The findings are drawn from empirical data collected from 15 unstructured in-depth interviews with NTS of the School of Computing and Informatics Technology at Makerere University, and analysed with the aid of qualitative data analysis software ATLAS.ti. Three major findings were established: (1) motivations were found to be multiple, multifaceted and varied for each individual; (2) the sociocultural context of the African society including societal perceptions of university education were found to be the major factor shaping motivations of NTS to upgrade their educational qualifications; and (3) most motivations were found to be extrinsic in nature rather than intrinsic and based more on push rather than pull factors. Yet, although the demand for university education is increasing, life beyond university can no longer guarantee some of the anticipated rewards such as employment and its related benefits. It therefore becomes important that the purpose of education within universities in Africa is directed towards achieving development of the whole human being. In this way, a graduate's capacity to function will not be seen only in the economic and professional life, but also in other spheres of life.